Carotid ultrasound following transcarotid transcatheter aortic valve replacement. (1st July 2022) - Panagides, Vassili; Kalavrouziotis, Dimitri; Dumont, Eric; Delarochellière, Robert; Paradis, Jean-Michel; Mesnier, Jules; Mohammadi, Siamak; Rodés-Cabau, Josep
Abstract: Background: Transcarotid (TC) is a common alternative access for transcatheter aortic valve replacement (TAVR) when the transfemoral route is not suitable. However, scarce data exist on systematic ultrasound (US) follow-up of these patients. This study aims to evaluate the safety of TC-TAVR using pre-and post-procedure carotid artery US assessment. Methods: We performed an observational prospective study including 50 consecutive patients who underwent TC-TAVR that had a follow-up at our institution between September 2016 and July 2020. Results: All patients had a carotid US examination at a median time of 13 months (IQR: 5–17) following the procedure. Thirty-six (71%) patients also had a US examination prior to the procedure. Mean pre-procedural access route common carotid artery (AR-CCA) peak systolic velocity (PSV) was 62.9 cm/s (SD:16.8) vs. 69.0 cm/s (SD: 53.4) in the contralateral CCA (CL-CCA), p  = 0.562). There was a significant increase in post-procedural PSV values in the AR-CCA (30.3 cm/s (SD: 36.3), p  < 0.001) but not in the CL-CCA (5.8 cm/s (SD: 51.7), p  = 0.503). Two new carotid stenoses (4%) were diagnosed after the procedure. No baseline or procedural variables were associated with a higher increase in carotid flow velocities at follow-up. There were no cerebrovascular events related to these findings after a median follow-up of 29 months (IQR:13–33). Conclusions: TC-TAVR was associated with a mild but significant increase in carotid flow velocities, with new significant (>50%) carotid stenosis diagnosed in 4% of patients. These findings were not associated with clinical events after a median follow-up of 2 years. Further studies are warranted. Highlights: Peak systolic velocities of the carotid artery increase after TC-TAVR. New carotid stenosis (>50%) were diagnosed in 4% of patients after TC-TAVR. No adverse events related to these findings occurred.